2016
DOI: 10.3102/0013189x16633441
|View full text |Cite
|
Sign up to set email alerts
|

Public Pre-K and Test Taking for the NYC Gifted-and-Talented Programs

Abstract: The New York City Department of Education (NYC DOE) gifted-and-talented programs aim to support all students of exceptional learning potential within the public school system. Using proprietary data made available to us by the NYC DOE, we show, however, that substantial disparities exist in the rates of gifted-and-talented admission test taking, the first step in the process of accessing these more challenging educational opportunities. While Black and Latino/a students take the test for gifted-and-talented ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 34 publications
(46 reference statements)
0
19
0
Order By: Relevance
“…Other good examples of how research can influence the policy cycle are universal screening for gifted education programming and the use of growth models in state accountability systems. Regarding universal screening, despite abundant research on the problems of relying on teacher nominations for identification (e.g., Card & Guiliano, 2015; Grissom & Redding, 2016; Lu & Weinberg, 2016; McBee, Peters, & Miller, 2016), universal testing has generally not yet been adopted. Efforts are underway in states such as Illinois to use this research to establish state-level policies that encourage or even require universal screening in high-poverty districts.…”
Section: Areas In Need Of Additional Policy Researchmentioning
confidence: 99%
“…Other good examples of how research can influence the policy cycle are universal screening for gifted education programming and the use of growth models in state accountability systems. Regarding universal screening, despite abundant research on the problems of relying on teacher nominations for identification (e.g., Card & Guiliano, 2015; Grissom & Redding, 2016; Lu & Weinberg, 2016; McBee, Peters, & Miller, 2016), universal testing has generally not yet been adopted. Efforts are underway in states such as Illinois to use this research to establish state-level policies that encourage or even require universal screening in high-poverty districts.…”
Section: Areas In Need Of Additional Policy Researchmentioning
confidence: 99%
“…Second, knowing "how many" gifted students there are helps serve as a benchmarking assessment of how well identification practices are (or are not) working. Several recent studies (e.g., Card & Guiliano, 2015;Grissom & Redding, 2016;Lu & Weinberg, 2016) have described differences in rates of gifted identification for different demographic groups. The identification of "excellence gaps" of high performance on standardized tests (Plucker, Hardesty, & Burroughs, 2013;Plucker & Peters, 2016) has also garnered substantial attention.…”
Section: Proportion Giftedmentioning
confidence: 99%
“…Notably, the authors showed that disparities in G & T test-taking were one of the greatest contributors to differential access to G & T programs. Using a logistic regression framework, Lu and Weinberg (2016) also showed that participation in a New York City public pre-K program, including full-time and part-time pre-K classrooms within district schools, and other publicly funded community-based pre-K centers, was significantly correlated with higher G & T test-taking. Additionally, racial, socioeconomic, and language-based gaps in G & T test-taking were further mitigated among those who attended public pre-K programs compared with those who did not.…”
mentioning
confidence: 96%
“…Many researchers have found that socioeconomic and racial/ethnic achievement gaps are large at school entry and remain consistent across schooling (Reardon & Portilla, 2016; von Hippel et al, 2018). There are also significant disparities in access to G & T programs among students from disadvantaged backgrounds (Card & Giuliano, 2016; Ford, 1996, 1998; Ford et al, 2008; Ford & Harmon, 2001; Lu & Weinberg, 2016). Extant work has shown that earlier identification of giftedness may hold greater promise for enabling children from all backgrounds to fulfill their academic potential in the longer term (Goldhaber & Brewer, 1997; Meyer, 1999; Phillips, 1997; Phillips, 2013; Phillips & Chin, 2004; Raudenbush & Eschmann, 2015; Rivkin et al, 1998; Tach & Farkas, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation